Analisis Kelayakan Usaha Lontong Tuyuhan Di Desa Tuyuhan Kecamatan Pancur Kabupaten Rembang - Ummukifdiyah Rohmatul Huda; Parikesit Penangsang (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This study aims to assess the feasibility of the Lontong Tuyuhan MSME business which has a location in Tuyuhan Village, Rembang Regency in Pancur District. The data analysis methods used are revenue analysis, profit analysis, cost analysis, and also business feasibility analysis using the Revenue Cost Ratio (R/C Ratio), Return On Investment (ROI), and Benefit Cost Ratio (B/C Ratio) analysis tools. ). This study uses qualitative research methods with primary data collection tools in the form of observation, questionnaires, interviews, and documentation. Data was obtained through 6 informants, namely the owner of the Lontong Tuyuhan MSME business which has a location in Tuyuhan Village, Rembang Regency in Pancur District. The Lontong Tuyuhan MSME business that has been researched can be said to be adequate to run with an average R/C Ratio of 2.11 B/C Ratio of 1.11 and ROI of 171.30%. The Lontong Tuyuhan MSME business that was observed had an estimated average revenue of IDR 31,322,500/month. With an average monthly capital excluding initial capital with a nominal value of IDR 14,893,425/month and an average profit of IDR 16,429,075/month.